Influência de plantas entomófilas sobre a comunidade de artrópodes associada ao morangueiro (Fragaria x ananassa Duch) em cultivo convencional - Oliveira, Pablo Garcia de (2019)
The objective of this work was to evaluate the effect of basil (Ocimum basilicum), mix of asteraceae calendula (Calendula officinalis) and marigold (Tagetes erecta), and coriander (Coriandrum sativum) plants on the arthropod community associated with strawberry in conventional crop. For this, arthropods were collected in basil, asteraceae and coriander plants, as well as in strawberry plants in the following five treatments: T1) strawberry under the influence of basil plants, T2) strawberry under the influence of basil/mix of asteraceae, T3) strawberry under the influence of asteraceous mix, T4) strawberry under the influence of mix of asteraceae/coriander, and T5) strawberry under the influence of coriander plants. Between April and August 2018, weekly collections were carried out to evaluate the abundance, richness, diversity and functional groups in each monitored area. We collected 19,750 arthropods distributed in 185 taxa. There was a significant difference for the abundance between entomophilous plants, obtaining higher average in asteraceae plants. Regarding the ecological strategy, there was a significant difference between the average abundance of phytophagous, parasitoids and pollinators associated to the mix of asteraceae, C. sativum and O. basilicum. Higher average abundance of phytophages and parasitoids were found in the mix of asteraceae and coriander, while the highest average of pollinators was observed in basil. There was no significant difference between the indices of abundance, richness, Shannon and the ecological niches within the regions of influence in the strawberry. A significant difference was found between the means of abundance and Shannon of the mix of asteraceae and T3 and coriander and T5. Regarding the functional groups, there was a significant difference between the pollinators average abundance present in basil and T1. Among the pollinators collected, Apis mellifera was the most abundant, both in entomophilous plants (80%) and strawberry (71%). The mean abundance of phytophagous and parasitoids differed between asteraceae and T3 and between C. sativum and T5, observing a greater abundance of phytophagous and parasitoids in the asteraceae and coriander mix. Although these entomophilous plants harbor larger numbers of parasitoids, there was no higher abundance or richness in adjacent strawberry plants. Among the arthropods collected, the thrips were the most abundant (8,027 individuals), with 80.35% associated with entomophilous plants. There was a significant difference between the abundance of thrips in the entomophilous plants and in the strawberry, obtaining higher averages in the entomophilous plants. Thus, plants of C. officinalis, C. sativum, O. basilicum and T. erecta may have acted as a trap crop or refuge for thrips when distributed inside the strawberry conventional crop. Regarding the similarity, it was observed that basil, asteraceae and coriander mix plants presented lower similarity with their regions of influence on the strawberry. Therefore, the entomophilous plants exerted little influence on the arthropod community associated to the strawberry in conventional cultivation, when distributed in small spots inside the culture and under chemical control conditions.